Understanding Youth and Adolescent Overweight and Obesity: Resources for Families and Communities - Jamie Eisenberg; Heidi Liss Radunovich; Mark A. Brennan (EDIS)
FCS8839, a 7-page fact sheet by Jamie Eisenberg, Heidi Liss Radunovich, and M. A. Brennan, explores the alarming rise in childhood and adolescent overweight and obesity and helps parents and educators understand the issue. Explains who is defined as overweight and obese, defines potential causes and contributors to the problems, and lists ways that parents and leaders can help. Published by the UF Department of Family, Youth and Community Sciences, April 2007.